Strengthening Al-Islam Kemuhammadiyahan Character Education through the ‘Magic Fingers’ Media in Addition Learning among Elementary School Students: Penguatan Pendidikan Karakter Al-Islam Kemuhammadiyahan melalui Media Jari Ajaib pada Materi Penjumlahan Siswa Sekolah Dasar - Nurul Nujum; Dien Nurmarina Malik Fadjar (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
Character education is a fundamental pillar in shaping students’ personality, especially at the primary level where basic values are first internalized. This classroom action research aimed to describe the effectiveness of the “Jari Ajaib” (Magic Fingers) instructional media in strengthening character education based on Al-Islam and Kemuhammadiyahan (AIK) values through addition learning in Grade 1 students at SD Negeri 13 Kota Sorong. The study employed a qualitative–quantitative descriptive approach within a classroom action research framework. The participants were 21 students, and data were collected using character observation sheets, semi-structured interview guidelines for teachers and students, documentation of learning activities, and a simple addition test administered before and after the intervention. Data were analyzed using qualitative descriptive techniques for character development and simple descriptive statistics for students’ understanding of addition. The findings indicate improvement in students’ responsibility, cooperation, honesty, discipline, and empathy during learning activities using the Jari Ajaib media, accompanied by better accuracy and confidence in performing addition tasks. The explicit integration of AIK values also contributed to an engaging, joyful, and spiritually meaningful learning atmosphere. These results suggest that mathematics instruction can function not only to strengthen cognitive abilities but also as an effective vehicle to cultivate students’ religious character through contextual integration of AIK values in everyday classroom practice.